In vitro antibacterial activity and beta-lactamase stability of SY5555, a new oral penem antibiotic. - Inoue, E (1994)
The antibacterial activity of SY5555, a new oral penem antibiotic, was compared with those of cefaclor, cefixime, and cefteram. SY5555 was more active than the comparison agents against methicillin-susceptible Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pneumoniae, Enterococcus faecalis, Citrobacter freundii, Enterobacter cloacae, Morganella morganii, Acinetobacter calcoaceticus, Clostridium spp., and Bacteroides fragilis. Against Providencia spp., Proteus spp., and Haemophilus influenzae, SY5555 was less active than cefixime or cefteram. SY5555 was inactive against methicillin-resistant S. aureus. Enterococcus faecium, Serratia marcescens, Pseudomonas aeruginosa, and Xanthomonas maltophilia, as were the comparison agents. The bactericidal activities of SY5555, cefixime, and cefteram were at or slightly greater than the MICs for clinical isolates of Escherichia coli and Klebsiella pneumoniae. SY5555 was not hydrolyzed by various types of beta-lactamases. However, SY5555 and the comparison agents were hydrolyzed by X. maltophilia (L-1) and P. aeruginosa/pMS354 beta-lactamases, two Bush group 3 beta-lactamases, SY5555 showed a high affinity, as did cefixime and cefteram, for cephalosporinases from C. freundii GN7391 and E. cloacae GN7471 strains. These results suggest that SY5555 may be more specific than existing beta-lactam antibiotics.